Andrea Cesalpino's De plantis libri XVI (1583) and the transformation of medical botany in the 16th century : edition, translation, and commentary on Book I - Cesalpino, Andrea, 1519-1603 (Medical traditions,, 2023)
In 1583 the Italian botanist and physician Andrea Cesalpino (1524-1603) published De Plantis Libri XVI, made of 16 books (libri), considered to be the first treatise where botany is treated independently from medicine. In so doing, he broke with a long tradition inherited in Western science from Antiquity and perpetuated during the Middle Age through the early Renaissance. De Plantis lays the foundations of scientific systematics through a new focus on plant morphology and natural similarities and became a milestone in the history of Western botany. It is a precious testimony to the evolution of botanical and physiological knowledge in the Middle Ages and the Renaissance and illustrates the role of Aristotelian philosophy in 16th-century knowledge. The volume includes an introductory essay about Cesalpino's philosophy and botany, a critical edition of the Latin text, a translation, a commentary, and indexes. It should interest scholars in Renaissance studies, historians, and philosophers of science and medicine, as well as botanists and plant scientists curious about the history of plant sciences.